ENHANCED RECOVERY AFTER CAESAREAN SECTION - AN IMPROVED PATHWAY THAN CONVENTIONAL CARE FOR REDUCING HOSPITAL STAY - Uzma Afreen; Fazal e Karim Faisal; Khan, Maliha Khalid; Zahid Akhtar Rao; Rozina Mustafa; Sanober Afreen (Journal of Ayub Medical College Abbottabad, 2024)
Background: With the help of an evidence-based approach called Enhanced Recovery After Surgery (ERAS), patients can receive standardised perioperative care and recover more quickly. Many surgical specialties, such as orthopaedics, gynaecological onco-surgery, breast surgery, urology, and colorectal surgery, use ERAS protocols extensively. Improved postoperative recovery has been shown to be beneficial in lowering hospital stays, costs, and increasing patient satisfaction. This study sought to determine whether the application of an enhanced recovery after surgery (ERAS) protocol for patients having an elective caesarean section would improve the patients’ postoperative status regarding pain management, length of stay in the hospital and expenses associated with complications. Methods: A prospective study was conducted in PAF Hospital Faisal, Karachi. Women scheduled for elective caesarean sections were enrolled in the cross-sectional study from February 2023 to July 2023, and they were compared to women who had caesarean sections during the same time period and received conventional perioperative care. Patients with medical or surgical comorbidities, as well as women who had emergency or urgent caesarean sections, were excluded. The surgical method was same in both ERAS and non-ERAS arms. Intravenous hydration was used to achieve a specific purpose. After 4 hours, liquids were introduced, followed by solids after 6 hours. Intravenous paracetamol and intramuscular diclofenac were given regularly. After 6-8 hours, the Foleys catheter was withdrawn. The conventional care group fasted for 6 hours before and after surgery. The catheter was left in place for 24 hours, and 2500 ml of intravenous fluids were administered on the first day, followed by 1000 ml on the second. The length of hospital stay was determined by clinical criteria and the discretion of the care providers. Results: In contrast to the conventional care group, the ERAS arm experienced a much shorter post-operative hospital stay. (p-value= 0.001; 33.42 vs. 61.30 hours). The patient quickly recovered due to early eating, early ambulation, early catheter removal, multimodal pain management, and pre-emptive analgesia and antibiotic administration. Conclusion: The ERAS protocol has been shown to be beneficial in lowering postoperative pain and nausea, the average cost of hospitalization, and improving patient satisfaction. It seems to be worth implementing this protocol widely among patients undergoing elective caesarean sections